Pengaruh Model Problem-Based Learning Terhadap Kemampuan Berpikir Kritis Peserta Didik - Mula Sigiro; Gresia Ledy Sinaga; Rolan Manurung; Hebron Pardede (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
This study aims to determine whether there is an effect of the Problem-based learning model in physics learning on the critical thinking skills of class VIII students of SMP Negeri 1 Sei Bamban. This study uses a problem-based learning model and refers to indicators of critical thinking skills. The design used in this study was two group pretest-posttest. The research sample was 60 students. The data analysis technique used is descriptive analysis and inferential analysis using the t-test. The results showed that through the application of the problem-based learning model, the results of data analysis of students' critical thinking skills were in the very good category with an average score of 81.67% in the experimental class and in the control class the results of data analysis of students' critical thinking abilities were in the good category with an average score of 70.74%. So it can be concluded that the problem-based learning model can affect students' critical thinking skills.